Pengaruh Kreativitas, Inovasi, dan Transformasi Digital terhadap Kinerja Kewirausahaan Teknologi - Yeyen Ramadhan; Rian Hardiansyah (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines the influence of creativity (X1), innovation (X2), and digital transformation (X3) on technological entrepreneurship performance (Y) among micro, small, and medium enterprises (MSMEs) in Sumbawa Regency, Indonesia. Employing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0, data were collected from 100 purposively sampled MSME owners/managers using a validated Likert-scale questionnaire. Outer model evaluation confirmed convergent validity (AVE > 0.50; loadings > 0.70), discriminant validity (Fornell-Larcker criteria; HTMT < 0.85), and reliability (Cronbach's α > 0.89; composite reliability > 0.91). Inner model results revealed an R² of 0.426 (adjusted R² = 0.408), indicating substantial explanatory power. Hypothesis testing via bootstrapping (5,000 resamples) supported all paths: creativity (β = 0.292, t = 3.706, p < 0.001), innovation (β = 0.272, t = 3.632, p < 0.001), and digital transformation (β = 0.343, t = 3.840, p < 0.001)—the strongest predictor. Effect sizes were small to medium (f²: 0.118–0.169), with moderate predictive relevance (Q² = 0.230).​ Findings align with Resource-Based View and Dynamic Capabilities theories, underscoring digital transformation's dominance in bridging geographical constraints and enhancing market expansion, operational efficiency, and customer satisfaction in rural contexts. Theoretically, this integrates creativity-innovation-digital triad for technopreneurship; practically, it informs MSME training and policy for Sumbawa's digital ecosystem. Limitations include cross-sectional design; future research should explore longitudinal and moderating effects.